Effects of trait self-consciousness and perceived pressure on flow state in elite tennis players - Jacklin, C.; karageorghis, C. I. (Journal of Sports Sciences, 2004)
Es wurden die Auswirkungen von Selbstbewusstsein und empfundenem Druck auf den Flow-Status bei Elite-Tennisspielern (n=36) untersucht.